Model Diagnosis dan Rawatan Kemalangan Jalan Raya di Malaysia - Radin Sohadi, Radin Umar; Mahmud, Ahmad Rodzi; Adnan, Aminuddin (Universiti Putra Malaysia Press, 1993)
Absence of an information analysis system and a proper accident investigation framework have been the stumbling blocks in the investigation, evaluation and monitoring of accident problems in Malaysia. This paper presents the information system developed and provides the accident treatment model for implementation throughout Malaysia. Two police districts, Seremban and Shah Alam were chosen as a test case in this National Safety Council Pilot Project. Accident data are based on a police form POL27 (Pind 1/91) designed to enable processing and analysis using a customised microcomputer accident analysis package (MAAP). The system enables a thorough analysis of certain cases particularly on black spots. A dangerous location identification system based on accident maps, link-node-cell system and coordinates was used in the urban areas, while a kilometer post system was used for the rural highways. In-depth analysis on black spots could be achieved by means of a stick and collision diagram. This would enable diagnosis of actual causes of accidents at a problem location to be done expeditiously, more easily and more accurately so that